A comparison of the existing recommendations for human and veterinary clinicians on the management and prevention of the zoonotic aspects of dermatophytosis: A scoping review - Caroline O’Connor; Daisy Hollister; Richard Barlow; Hannah Wainman; Alison Ashmore; Lisa Morrow; Jenny Stavisky; Kathryn Griffiths; Christina Kuhl; Marnie L. Brennan (PLoS ONE, 2026)
Background Dermatophytosis (or ringworm) is a highly infectious zoonotic disease commonly found in humans and multiple animal species globally. With children under 5 years of age being the most at risk human patient group, and dermatophytosis the zoonosis most frequently contracted by veterinary professionals in the UK from their patients, it is of significance to both human and animal patients. Little is known as to whether there is recognition in both human medical and veterinary guidance of the importance of their opposite clinical counterpart. In addition, it is unknown whether the recommendations for zoonotic disease management and prevention are complementary between the two disciplines. Objectives The aim of this scoping review was to assess all human medical and veterinary guidelines pertaining to zoonotic dermatophytosis, to explore how the zoonotic aspects of the disease were reported and to determine if there was conflicting or complementary advice between the two disciplines on disease management and prevention. Sources of evidence: Medline, CAB Abstracts, and Embase were searched for relevant literature and the results assessed and filtered using inclusion and exclusion criteria. A targeted grey literature search was also performed. Eligibility criteria To be included, broadly all publications had to mention dermatophytes or specifically named dermatophyte species, and mention ‘guidelines’ or ‘protocols’. Publications needed to also mention terms relating to ‘zoonoses’; for veterinary publications, be focused on cattle, dogs and cats and for human medical publications, mention the clinical manifestation of dermatophytosis (e.g. tinea capitis). Some mention of risk factors for zoonotic transmission needed to also be included. Charting methods A data charting form was used to extract data pertaining to dermatophyte species discussed, animal species discussed, prevalence and risk factors, zoonotic risk factors, zoonotic recommendations for humans, transmission, diagnostic testing, treatment, monitoring response to treatment, and prevention and management from the included studies. A critical appraisal process using the AGREE II tool was conducted to identify the common limitations of the shortlisted published papers. Results Of the 554 human and 137 veterinary publications screened, 5 of each publication source met the inclusion criteria. Although data were charted across several variables, none of the publications used an evidence-based guideline approach in their construction (e.g. GRADE, AGREE processes) and a significant proportion of papers provided limited supporting evidence for their recommendations. There were significant gaps and minimal synergies between veterinary and human medicine recommendations. The human literature had limited information pertaining to zoonotic recommendations. Discussion A minimal number of studies have been conducted regarding zoonotic dermatophytosis, both in human medical and veterinary disciplines. There is a lack of good quality, detailed information about the prevention and management of the zoonotic aspects of the disease, indicating that there is a need for the development of evidence-based guidelines to support human and veterinary clinicians making decisions about these patients. Conclusion Evidence-based guidelines, inclusive of high quality information pertaining to the zoonotic aspects of the disease for both humans and animals, should be generated. Ideally human and veterinary representatives would work together to generate cohesive and complementary guidance.